1994
DOI: 10.1007/bf01183866
|View full text |Cite
|
Sign up to set email alerts
|

A time course study of the alterations in the development of the hamster cerebellar cortex after destruction of the overlying meningeal cells with 6-hydroxydopamine on the day of birth

Abstract: This study is a chronological analysis of 6-hydroxydopamine-induced alterations in development of the hamster cerebellar cortex. This treatment destroys the overlying meningeal cells, the sequelae of which include (i) a thinning of the external granular layer over the folial apices and a thickening in the region of the prospective fissures, reflecting a retardation of the growth of the cerebellar cortex, accompanied by displacement of the normally superficialmost GFAP-positive external granular layer cells int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The cerebellar phenotype in Gpr56 −/− mice is strikingly similar to those observed when the meninges overlying the cerebellum are ablated at birth using 6-hydroxydopamine (Sievers et al, 1985; von Knebel Doeberitz et al, 1986; Sievers et al, 1994b). This raises the intriguing possibility that the meninges are necessary for GPR56 function in rostral cerebellar development, potentially as a source of the GPR56 ligand.…”
Section: Discussionmentioning
confidence: 53%
“…The cerebellar phenotype in Gpr56 −/− mice is strikingly similar to those observed when the meninges overlying the cerebellum are ablated at birth using 6-hydroxydopamine (Sievers et al, 1985; von Knebel Doeberitz et al, 1986; Sievers et al, 1994b). This raises the intriguing possibility that the meninges are necessary for GPR56 function in rostral cerebellar development, potentially as a source of the GPR56 ligand.…”
Section: Discussionmentioning
confidence: 53%
“…A number of studies have shown that the pial BL is crucial for neocortical development. Removal of the BL leads to detachment of RGC fibers, affecting RGC survival and cortical lamination von Knebel Doeberitz et al 1986;Sievers et al 1994;Radakovits et al 2009). Laminins are major components of the BL (Timpl et al 1979) and are also present in the VZ of the developing neocortex (Campos et al 2004;Lathia et al 2007).…”
Section: Lamininsmentioning
confidence: 99%
“…The loss of lamination observed in many caecilian species (Wake 1985) may be a consequence of the alteration of retinal glial structures. Indeed, intact radial glial structures are necessary for the formation of neuronal layers in the cerebellum (Rakic 1971;Hatten 1990;Sievers et al 1994). The initial changes observed in caecilian retinal Müller cells might involve those of the cytoskeleton, e.g.…”
Section: Gfap-immunonegative Müller Cellsmentioning
confidence: 99%